ŞTEFAN NICULESCU, EULOGIZED IN GERMANY FOR HIS CONTRIBUTION TO THE CURRENT EUROPEAN MUSICAL HERITAGE - Sanda Valentina HÎRLAV-MAISTOROVICI (Studia Universitatis Babeş-Bolyai. Musica, 2015)
The volume “Ştefan Niculescu”, published in 2013 by BIS-Verlag der Carl von Ossietzky Universität Oldenburg, edited by Eva-Maria Houben, Michael Heinemann and Violeta Dinescu, is part of a series entitled Archiv für osteuropäische Musik. Quellen und Forschungen, translatable as The East European Music Archive. Sources and Research. This series of volumes seeks to offer a bird’s-eye view over contemporary classical music from an intercultural perspective, bringing together its Eastern and Western European roots. An essential contribution to this project belongs to Violeta Dinescu, currently a professor and doctoral advisor at the above mentioned university.